2017
DOI: 10.1016/j.watres.2017.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Efficient treatment of perfluorohexanoic acid by nanofiltration followed by electrochemical degradation of the NF concentrate

Abstract: The present study was aimed at the development of a strategy for removing and degrading perfluorohexanoic acid (PFHxA) from industrial process waters at concentrations in the range 60-200 mg L. The treatment train consisted of nanofiltration (NF) separation followed by electrochemical degradation of the NF concentrate. Using a laboratory-scale system and working in the total recirculation mode, the DowFilm NF270 membrane provided PFHxA rejections that varied in the range 96.6-99.4% as the operating pressure wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(80 citation statements)
references
References 59 publications
(57 reference statements)
2
78
0
Order By: Relevance
“…17 Therefore, treatment of the concentrate laden with PFASs and other contaminants remains a challenge and is considered one of the main limitations of membrane filtration. 12,[18][19][20] Few studies exist evaluating differences in PFAS adsorption of both GAC and AIX sorbents in a direct comparison. Even fewer studies exist combining full-scale membrane techniques with pilot-scale GAC and AIX filters, respectively, even though this treatment set-up is being discussed as having the potential to be a new standard approach for the removal of PFASs in full-scale drinking water treatment.…”
Section: Water Impactmentioning
confidence: 99%
“…17 Therefore, treatment of the concentrate laden with PFASs and other contaminants remains a challenge and is considered one of the main limitations of membrane filtration. 12,[18][19][20] Few studies exist evaluating differences in PFAS adsorption of both GAC and AIX sorbents in a direct comparison. Even fewer studies exist combining full-scale membrane techniques with pilot-scale GAC and AIX filters, respectively, even though this treatment set-up is being discussed as having the potential to be a new standard approach for the removal of PFASs in full-scale drinking water treatment.…”
Section: Water Impactmentioning
confidence: 99%
“…which is significantly reduced to 153 kWh/m 3 when the target PFASs removal rate is set at 98% (treatment time 6 h). Therefore, energy consumption, that is strongly dependent on the target PFASs removal rate [55], and the potential formation of disinfection byproduct could be considered the main drawbacks of the electrochemical treatment. In this way it is demonstrated that the electrochemical treatment of the industrial WWTP effluent with BDD anodes allows the effective removal of PFASs at the same time that the general TOC content is nearly completely eliminated.…”
Section: Paying Attention Tomentioning
confidence: 99%
“…The alternative approaches are emerging as more mobile options using small‐scale plants, which could be applied at sites where PFAS waste concentrates are generated. Based on numerous sources, an approximate range of energy demand per volume treated for plasma, electrochemical treatment, and sonolysis is 0.01 to 0.5‐kW h per liter (kW‐h/L; 0.04 to 1.9 kW‐h per gallon [kW‐h/gal]; e.g., Gomez‐Ruiz et al ; Soriano et al ; Kempisty et al ; Nzeribe et al ; Singh et al , ). However, approximating a range of energy demand for these relevant technologies is difficult to accurately summarize due to the variety of operating conditions within the respective studies when the energy demand was determined.…”
Section: Identifying the Destructive Technology “Strike Zone”mentioning
confidence: 99%
“…, ), electrochemical treatment (Schaefer et al. ; Soriano et al ; Schaefer et al ; Pica et al. ; Schaefer et al ), and sonolysis (Vecitis et al ; Campbell et al.…”
Section: Considerations For Available Pfas‐relevant Destruction Technmentioning
confidence: 99%
See 1 more Smart Citation